Divergences in Macrophage Activation Markers Soluble CD163 and Mannose Receptor in Patients With Non-cirrhotic and Cirrhotic Portal Hypertension - Ørntoft, Nikolaj Worm; Blé, Michel; Baiges, Anna; Ferrusquia, Jose; Hernández-Gea, Virginia; Turon, Fanny; Magaz, Marta; Møller, Søren; Møller, Holger Jon; Garcia-Pagan, Juan Carlos; Gronbaek, Henning (Frontiers in Physiology, 2021)
Introduction: Macrophages are involved in development and progression of chronic liver disease and portal hypertension. The macrophage activation markers soluble (s)CD163 and soluble mannose receptor, sMR, are associated with portal hypertension in patient with liver cirrhosis but never investigated in patients with non-cirrhotic portal hypertension. We hypothesised higher levels in cirrhotic patients with portal hypertension than patients with non-cirrhotic portal hypertension. We investigated sCD163 and sMR levels in patients with portal hypertension due to idiopathic portal hypertension (IPH) and portal vein thrombosis (PVT) in patients with and without cirrhosis. Methods: We studied plasma sCD163 and sMR levels in patients with IPH (n=26), non-cirrhotic PVT (n=20), patients with cirrhosis without PVT (n=31) and with PVT (n=17), and healthy controls (n=15). Results: Median sCD163 concentration was 1.51 (95%CI:1.24-1.83) mg/L in healthy controls, 1.96 (95%CI:1.49-2.56) in patients with non-cirrhotic PVT and 2.16 (95%CI:1.75-2.66) in patients with IPH. There was no difference between non-cirrhotic PVT patients and healthy controls, whereas IPH patients had significantly higher levels than controls (P<0.05). The median sCD163 was significantly higher in the cirrhotic groups compared to the other groups, with a median sCD163 of 6.31 (95% CI: 5.16-7.73) in cirrhotics without PVT and 5.19 (95% CI: 4.18-6.46) with PVT (P<0.01, all). Similar differences were observed for sMR. Conclusions: Soluble CD163 and sMR levels are elevated in patients with IPH and patients with cirrhosis, but normal in patients with non-cirrhotic PVT. This suggests that hepatic macrophage activation is primarily driven by structural liver damage per se and not portal hypertension.